Neurodevelopmental Disorders (NDD) Caused by Genomic Alterations of the Ubiquitin-Proteasome System (UPS): the Possible Contribution of Immune Dysregulation to Disease Pathogenesis - Ebstein, Frédéric; Küry, Sébastien; Papendorf, Jonas Johannes; Krüger, Elke (Frontiers in Molecular Neuroscience, 2021)
Over thirty years have passed since the first description of ubiquitin-positive structures in the brain of patients suffering from Alzheimer’s disease. Meanwhile, the intracellular accumulation of ubiquitin-modified insoluble protein aggregates has become an indisputable hallmark of neurodegeneration. However, the role of ubiquitin and a fortiori the ubiquitin-proteasome system (UPS) in the pathogenesis of neurodevelopmental disorders (NDD) is much less described. In this article, we review all reported monogenic forms of NDD caused by lesions in genes coding for any component of the UPS including ubiquitin-activating (E1), -conjugating (E2) enzymes, ubiquitin ligases (E3), ubiquitin hydrolases, ubiquitin-like modifiers as well as proteasome subunits. Strikingly, our analysis revealed that a vast majority of these proteins have a described function in the negative regulation of the innate immune response. In this work, we hypothesize a possible involvement of auto inflammation in NDD pathogenesis. Herein, we discuss the parallels between immune dysregulation and neurodevelopment with the aim at improving our understanding the biology of NDD and providing knowledge required for the design of novel therapeutic strategies.